EMANCYPACJA RELIGIJNA A PERCEPCJA ROLI KOBIETY W SYTUACJI MIGRACYJNEJ NA PRZYKŁADZIE POLSKICH MIGRANTEK W ISLANDII - Inga Koralewska (Studia Humanistyczne AGH, 2016)
According to my research, not only migrants’ understanding of religiosity changes in migratory situation, but also the understanding of their agency in this process. Migrants position themselves as active agents and individually define their religiosity anew. As was stated, their new religiosity is individual and not institutional. There are certain grounds for supposing, that migratory experience plays a vital role in the process of religious emancipation. Goal of the paper is to answer the question whether migratory situation, apart from being a source of religiosity change, contributes also to change in attitudes towards gender roles in society. The answer is based on qualitative research conducted in years 2012–2015 in Iceland.